Evaluation of the level of antithrombin in patients with glomerulonephritis and nephrotic syndrome: A cross-sectional study - I. Mykhaloiko; R. Yatsyshyn; I. Dudar; H. Kuryliv (Ukrainian Journal of Nephrology and Dialysis, 2024)
The present study aimed to evaluate the level of antithrombin (AT)-III in blood serum in patients with primary glomerulonephritis (GN) and nephrotic syndrome (NS) and to assess its correlation with markers of NS and hypercoagulation.Methods. We conducted a cross-sectional observational study involving 76 patients with primary GN and NS admitted to the Ivano-Frankivsk Regional Clinical Hospital (Ukraine) in 2022–2024. The inclusion criteria were: age over 18 years, <1 month since the diagnosis of NS, and glomerular filtration rate (GFR) > 60 ml/min/1.73m². During the study, all patients underwent a standard examination, which included general clinical, biochemical, and instrumental research methods. A photometric assay of AT-III in serum using a chromogenic substrate was conducted with a set of reagents from “Granum” (Ukraine).Results. Normal levels of AT-III were identified in 24 patients (31.6%; 95% CI: 21.4–43.3), while decreased levels were found in 52 patients (68.4%; 95% CI: 56.7–78.6). Correlation analysis revealed a direct moderate correlation between serum albumin levels and AT-III levels (r = 0.535, p < 0.05), an inverse moderate correlation between daily protein excretion (DPE) and AT-III levels (r = -0.414, p < 0.05), and an inverse moderate correlation between the albumin/creatinine ratio (ACR) in urine and AT-III levels (r = -0.467, p < 0.05).Conclusions. In this cohort of patients with primary GN and NS, 68.4% exhibited decreased AT-III levels, indicating that AT-III deficiency is a common finding. The observed reduction in AT-III levels was significantly correlated with lower serum albumin levels, higher DPE, and higher ACR in urine. No significant association was found between AT-III deficiency and specific histological variants of GN, suggesting that the relationship between AT-III levels and hypercoagulopathy in GN and NS may be independent of the underlying glomerular pathology. The detected AT-III deficiency may warrant consideration for anticoagulant prophylaxis in patients with GN and NS. However, further studies are needed to determine whether AT-III levels can reliably guide anticoagulation therapy and reduce thromboembolic risk in this population.